EFFECTIVENESS OF STRUCTURED TEACHING PROGRAMME ON KNOWLEDGE OF POLYCYSTIC OVARIAN SYNDROME AMONG ADOLESCENT GIRLS - A., Sowmya M.; Fernandes, Philomena (Journal of Health and Allied Sciences NU, 2013)
The study was conducted to assess the effectiveness of structured teaching programme on knowledge of polycystic ovarian syndrome among adolescent girls. The study design adopted was pre experimental one group pre-test post- test design. The demographic Proforma were collected from the adolescent girls by using structured knowledge questionnaire. Data obtained in these areas were analysed using descriptive and inferential statistics. A significant difference between pre test and post test knowledge was found (t79= 2.0 p<0.05).The study findings showed that the structured teaching programme was effective in improving knowledge of adolescent girls regarding polycystic ovarian syndrome. There was no significant association between the level of knowledge and demographic variables except the group in which they study (Science, Arts, Commerce)
Keywords: knowledge; structured teaching programme; PCOS